A clinical and radiological long‐term follow‐up study of narrow diameter implants in the aesthetic area. (19th June 2018) - Trbakovic, Amela; Bongenhielm, Ulf; Thor, Andreas
Abstract: Purpose: To study long‐term function of narrow diameter implants (NDI:s) and if reduced implant‐tooth distance negatively impacts adjacent teeth. Materials and Methods: A clinical and radiological follow‐up of NDI:s replacing maxillary laterals and mandibular incisors was performed. Subjects that received 3.0‐3.3 mm‐diameter single implants from 3 units in Uppsala and Västerås, Sweden, between 2002 and 2011 were offered to participate in this retrospective study. Results: Twenty‐seven patients (30 implants) underwent clinical and CBCT examination, mean follow‐up time was 63.3 months. On average, the implant‐tooth distance was 1.6 mm at the cervical region and 17 implants were placed 1 mm or less to the adjacent root. Additionally, 2 patients (3 implants) underwent clinical examination (I). Twenty‐seven patients (36 implants) declined the examination but agreed to an interview (II). At the time of the follow‐up, all implants had good function, and implant survival of group I and II together was 97.2%. In both groups, the 2 main patient concerns were discoloration and regression of the buccal gingiva. Conclusion: Survival of implants is in accordance to standard diameter studies and although most implants were placed very close to the adjacent teeth, no pathologies could be linked to this except aesthetic concerns.